Nuclear translocation of activated MAP kinase is developmentally regulated in the developing Drosophila eye. - Kumar, J.P.; Hsiung, F.; Powers, M.A.; Moses, K. (Development, 2003)
In proneural groups of cells in the morphogenetic furrow of the developing Drosophila eye phosphorylated mitogen activated protein kinase (MAPK) antigen is held in the cytoplasm for hours. We have developed a reagent to detect nuclear MAPK non-antigenically and report our use of this reagent to confirm that MAPK nuclear translocation is regulated by a second mechanism in addition to phosphorylation. This "cytoplasmic hold" of activated MAPK has not been observed in cell culture systems. We also show that MAPK cytoplasmic hold has an essential function in vivo: if it is overcome, developmental patterning in the furrow is disrupted.